Deep Decision Forests of Radiomic Features for Automatic Contouring of Pelvic Anatomy for Prostate Radiotherapy - W. Macomber, M.; Phillips, M. H.; Tarapov, Ivan; Jena, R.; Criminisi, Antonio; J. Nyflot, M. (RSNA, 2018)
Deep Decision Forests of Radiomic Features for Automatic Contouring of Pelvic Anatomy for Prostate Radiotherapy